Pokorna, skromna, cicha… mądra? Literatura parenetyczna dla kobiet w szesnastowiecznej Anglii - Giza, Natalia (Biuletyn Historii Wychowania, 2012)
Renaissance in England is frequently referred to as the „Golden Age”, but despite countless innovative views and ideas, many aspects of social life did not develop simultaneously. The analysis of the 16th-century courtesy books for women enables readers to have a closer look at the Renaissance ideal of a perfect woman and the upbringing process, to which she was subjected in order to reach perfection. The most valued traits, defined mainly by men, still did not let women free themselves from stiff etiquette rules imposed on them several centuries earlier. While a man was spreading his Renaissance wings, a woman was silently staring at the ground beneath her feet.